1996
DOI: 10.1029/96gb00517
|View full text |Cite
|
Sign up to set email alerts
|

Effect of water management on methane emission from a Japanese rice paddy field: Automated methane monitoring

Abstract: The effect of differing water management schemes on the emission of methane (CH4) from rice paddies to the atmosphere was studied in a Japanese paddy field. Using an automated sampling and analyzing system, the test site was divided into two plots: a continuously flooded plot which was maintained flooded by constant irrigation from May to August, and an intermittently drained plot in which short‐term draining practices were performed several times during the flooding period . The draining practice had a strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
155
4
7

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 277 publications
(185 citation statements)
references
References 27 publications
19
155
4
7
Order By: Relevance
“…N 2 O concentration was determined with a gas chromatograph (Agilent 7890A). N 2 O emissions were calculated as the difference between 0 and 12 h based on the equation reported by Yagi et al (1996). Three bottles per treatment were destructively sampled at days 3, 7, 15, and 28 for soil samples.…”
Section: Gas and Soil Samplingmentioning
confidence: 99%
“…N 2 O concentration was determined with a gas chromatograph (Agilent 7890A). N 2 O emissions were calculated as the difference between 0 and 12 h based on the equation reported by Yagi et al (1996). Three bottles per treatment were destructively sampled at days 3, 7, 15, and 28 for soil samples.…”
Section: Gas and Soil Samplingmentioning
confidence: 99%
“…In fact, water regime (irrigation and drainage) affects directly soil characteristics, preventing or promoting the development of reductive conditions. The presence of standing surface water is essential for the development of the anaerobic conditions in paddy soil by limiting the transport of atmospheric oxygen into soil, which is favorable for CH4 production (Yagi et al, 1996;Bharati et al, 2001;Singh et al, 2009). Consequently, CH4 mitigation strategies from rice fields must consider rice agricultural practices and water regimes which reduce or limit the flooded period.…”
Section: Introductionmentioning
confidence: 99%
“…The authors suggest that the latter program of eleven intermittent drainage events reflects conventional Japanese rice cultivation in the region. There were no significant differences in nitrous oxide emissions or rice yields on the continuously flooded and intermittently drained plots in either year [181]. The authors conclude that water management can be an important methane mitigation measure, provided that rainfall is not excessive and farmers have adequate control of irrigation water deliveries.…”
Section: Intermittent Drainage Vs Continuous Floodingmentioning
confidence: 79%
“…Yagi et al [181] observed reductions in methane emissions of 42% and 45% in 1991 and 1993, respectively, on experimental plots in Kanto Province, Japan, that were drained at least two times during the season. Intermittent drainage was applied twice in 1991 and eleven times in 1993.…”
Section: Intermittent Drainage Vs Continuous Floodingmentioning
confidence: 99%